Elevated levels of cerebrospinal fluid neuron-specific enolase (NSE), but not S100B in major depressive disorder. (February 2015) - Schmidt, Frank Martin; Mergl, Roland; Stach, Barbara; Jahn, Ina; Schönknecht, Peter
Abstract Objectives. Alterations in neuronal and glial integrity are considered to be of pathogenic impact on major depressive disorder (MDD). For MDD, data on cerebrospinal fluid (CSF) levels of neuron-specific enolase (NSE) are lacking and scarce for glial protein S100B. Methods. We measured CSF levels of NSE and S100B in 31 patients with MDD and 32 mentally healthy controls using electrochemiluminescence immunoassays (ECLIA). Results. Adjusted means of NSE were significantly elevated in the MDD patients (11.73 ng/ml (9.95–13.52 95% CI) compared to the controls (6.17 ng/ml (4.55–7.78), F = 9.037, P = 0.004. Effect size for adjusted mean group difference of 5.57 ng/ml was found invariably high (Cohen's d = 1.23). Differentiating MDD from controls, a NSE cut-off of 7.94 ng/ml showed sensitivity of 81% (95% CI 63.7–90.8) and specificity of 75% (95% CI 57.9–86.7). Adjusted levels of S100B did not differ significantly between the two groups (1.12 ng/ml (0.77–1.48) in MDD, 0.97 ng/ml (0.64–1.30) in controls). Conclusions. Our results of elevated CSF-NSE levels support neuronal pathology in MDD and the potential use of CSF-NSE as marker in clinical diagnostics. Missing group differences in S100B do not promote a specific glial pathology in depressive disorders.